1998
DOI: 10.1055/s-2006-957514
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Properties of 16,17-Dihydroxybrachycalyxolide fromVernonia brachycalyx

Abstract: Extracts of the leaves from Vernonia brachycalyx showed in vitro activity against Plasmodium falciparum and promastigotes of Leishmania major. The germacrane dilactone 16,17-dihydrobrachycalyxolide (1) which was previously isolated from the aerial parts of the plant was shown to be the major antiplasmodial principle. An X-ray crystallographic analysis established the absolute configuration and some signals in the NMR spectra were reassigned. 16,17-Dihydrobrachycalyxolide (1) elicited a strong antiplasmodial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 7 publications
2
23
0
4
Order By: Relevance
“…(Gu et al, 1988) and Hypericum calcyinum L. (Decosterd et al, 1991) have shown in vivo and in vitro activity Kirkia wilmsii 3.7 No previous reports of antiplasmodial activity Lippia javanica 3.8 Reported to be a mosquito repellent (Govere et al, 2000), but no previous reports of antiplasmodial activity Ocimum americanum a 4.2 Used as a mosquito repellent (Seyoum et al, 2002) (Alves et al, 1997;Oketch-Rabah et al, 1998;Abosi and Raseroka, 2003;Kraft et al, 2003) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Gu et al, 1988) and Hypericum calcyinum L. (Decosterd et al, 1991) have shown in vivo and in vitro activity Kirkia wilmsii 3.7 No previous reports of antiplasmodial activity Lippia javanica 3.8 Reported to be a mosquito repellent (Govere et al, 2000), but no previous reports of antiplasmodial activity Ocimum americanum a 4.2 Used as a mosquito repellent (Seyoum et al, 2002) (Alves et al, 1997;Oketch-Rabah et al, 1998;Abosi and Raseroka, 2003;Kraft et al, 2003) …”
Section: Resultsmentioning
confidence: 99%
“…3.0 Several Vernonia species have shown activity in vitro and in vivo (Alves et al, 1997;Oketch-Rabah et al, 1998;Abosi and Raseroka, 2003;Kraft et al, 2003) Vernonia oligocephala 3.5 Several Vernonia species have shown activity in vitro and in vivo (Alves et al, 1997;Oketch-Rabah et al, 1998;Abosi and Raseroka, 2003;Kraft et al, 2003) a Naturalised in South Africa.…”
Section: Vernonia Myrianthamentioning
confidence: 99%
See 1 more Smart Citation
“…También se han identificado quinonas y triterpenos reportados con actividad antimicrobiana (Muñoz-Jáuregui, Ramos-Escudero, AlvaradoOrtiz, & Castañeda-Castañeda, 2007;Ramírez, Mendoza, Arreola, & Ordaz, 2010), así como también en el presente estudio, identificamos la presencia de sesquiterpenlactonas, las cuales se han reportado con actividad contra los parási-tos de la malaria y la leishmaniasis en ensayos in vitro (Oketch-Rabah et al, 1998;Sülsen, 2012;Cano de Terrones, 2014;Galarraga, Luis, Rojas, Offer, & Dobois, 2014).…”
Section: Discussionunclassified
“…[13][14][15][16] Estas duas classes de compostos, em particular as lactonas, são consideradas marcadores quimiotaxonômicos do gênero. [8][9][10][11][12]15 Inúmeras espécies de Vernonia são empregadas na medicina tradicional no tratamento de patologias diversas e como resultado, muitas têm sido investigadas do ponto de vista farmacológico, revelando importantes propriedades como antiplasmódica, [17][18][19] analgésica, antipirética e antiinflamatória, 20,21 antimicrobiana, [22][23][24] hiperglicêmica, 25 antioxidante 16 e vasodilatadora. 26 Vernonia chalybaea é uma planta de porte subarbustivo, com cerca de 1,0 m de altura e muito ramificada, freqüente na flora cearense.…”
Section: Introductionunclassified